Pengaruh Penerapan Standar Akuntansi Pemerintah dan Kualitas Aparatur terhadap Laporan Keuangan pada kantor Camat Pamatang Silima Kuta Kab. Simalungun - Mohd. Idris Dalimunthe (JURNAL MUTIARA AKUNTANSI, 2021)
This study aims to determine partially and simultaneously the effect of the adoption of government accounting standards (X1) and the quality of the local government apparatus (X2) on local government financial reports (Y). The type of research used is associative. The population in this study were all employees in the Pamatang Silima sub-district office, Simalungun Regency, as many as 70 people. The sample of this study is employees who meet the criteria of 32 employees. Types of data used in this study are primary data. The data source used in this study is primary data. The technique used by the author to collect the data needed in research is a questionnaire. This study uses multiple linear analysis techniques using SPSS Version 21. The results show that partially government accounting standards (X1) have a significant effect on local government financial reports, the quality of local government apparatus (X2) influences and not significantly on local government financial reports . And simultaneously government accounting standards and the quality of local government officials affect the financial statements of local governments.